A Case Study of Indonesia Electric Motorcycle in the Local Content Capabilities - Rendra, Meldi (JTERA (Jurnal Teknologi Rekayasa), 2023)
Firms always compete to add efficiency and effectiveness in generating products by links on supply-related costs or access to subtle knowledge to gain value added. Firms connect an island of industrial parts and knowledge to utilize supplementary unity in industrial clusters.Â  Competitors in industrial clusters outperform and strive to get evidence in the success levers. Good levers indicate excellent research, capacity, and transfer knowledge impacting inter-structured shift of success. Disseminative capability methods investigate and focus on the capabilities of the knowledge interaction as transfer performance. Partner will charge some of the key knowledge to transfer with know-how from industrial relevant work by communicating and deploying the practical grounding of fields. The concept will explain a picture of the knowledge giver and relevant measures of the capabilities. The knowledgeable process will present the theoretical stream of disseminative capabilities. Research findings have found the implication of disseminative capabilities and empirical results of Indonesia-styled weaknesses and strengths in deploying transfer knowledge. It will be helpful in the successful transfer of knowledge to gain a competitive advantage as a lesson learned. This case study will evaluate Karawang's manufacturing industry readiness for the electric motorcycle supply chain involves assessing infrastructure, technology, regulatory support, and workforce skills to determine its ability to meet market demands and international standards.